Epidermal growth factor receptor inhibition reduces angiogenesis via hypoxia-inducible factor-1α and Notch1 in head neck squamous cell carcinoma. - Wei-Ming Wang; Zhi-Li Zhao; Si-Rui Ma; Guang-Tao Yu; Bing Liu; Lu Zhang; Wen-Feng Zhang; Ashok B Kulkarni; Zhi-Jun Sun; Yi-Fang Zhao (PLoS ONE)
Angiogenesis, a marker of cancer development, affects response to radiotherapy sensibility. This preclinical study aims to understand the receptor tyrosine kinase-mediated angiogenesis in head neck squamous cell carcinoma (HNSCC). The receptor tyrosine kinase activity in a transgenic mouse model of HNSCC was assessed. The anti-tumorigenetic and anti-angiogenetic effects of cetuximab-induced epidermal growth factor receptor (EGFR) inhibition were investigated in xenograft and transgenic mouse models of HNSCC. The signaling transduction of Notch1 and hypoxia-inducible factor-1α (HIF-1α) was also analyzed. EGFR was overexpressed and activated in the Tgfbr1/Pten deletion (2cKO) mouse model of HNSCC. Cetuximab significantly delayed tumor onset by reducing tumor angiogenesis. This drug exerted similar effects on heterotopic xenograft tumors. In the human HNSCC tissue array, increased EGFR expression correlated with increased HIF-1α and micro vessel density. Cetuximab inhibited tumor-induced angiogenesis in vitro and in vivo by significantly downregulating HIF-1α and Notch1. EGFR is involved in the tumor angiogenesis of HNSCC via the HIF-1α and Notch1 pathways. Therefore, targeting EGFR by suppressing hypoxia- and Notch-induced angiogenesis may benefit HNSCC therapy.